Przestrzeń lokalna w prasie górnośląskiej XIX w. - Przyklenk, Joanna (Stylistyka, 2019)
The article is devoted to the Upper-Silesian space understood here not as the matter’s physical attribute, but as a cultural fact which delimits the area of incidents that the local press can include. It is an attempt to identify the textual strategies employed to demarcate the local borders – shared by the sender and the receiver. The strategies acknowledged to be the most interesting were those whose teleological dimension was subordinated to the journalistic practice of creating the sense of regional affinity. The research confirmed the thesis about the stylistic and genre unification of the Upper-Silesian press in the second half of the 19th century as stemming from the sociopolitical and cultural situation of the region, i.e., predominantly from the lack of the receivers’ reading skills, using the press as a political weapon, or publishers’ concern for winning the readers over. All of the above can be, thus, easily observed in the text, where appeals, addresses and persuasive resources are used in abundance. The analyses were focused on these elements which create the community of the Upper-Silesian region in the structure of the press message in a multifaceted way: the newspaper as a whole – the press column as a text – the press text. A number of newspaper titles were studied, which showed the strongly-stressed identification of the press makers with the local space – the Upper-Silesian one. The emotional style, explicitly expressed relationship with one’s own community and the use of the primarily spoken genre of speech (e.g., legend) in the written form make the bond stronger, whereas the whereas the goal of “taming” foreign topics was realized through, among others, the textual structure of enumeration or the dialogue. goal of “taming” foreign topics was realized through, among others, the textual structure of enumeration or the dialogue.